Transforming Presence: Seeing God’s body in Books I and II of Psalms - C. Brown Jones (Acta Theologica, 2021)
The Book of Psalms contains a significant amount of language and imagery related to the physical and sensing body of God. This article applies two questions to Books I and II of the Psalms. Related to God, what body language and imagery exist in these books? What might we make thereof? After a brief consideration of method, the article summarises the body language specific to God in Books I and II. Both books include several references to various parts of God’s head and to God’s arms, while there are fewer references to other body parts. Next, the article discusses the ways in which anthropomorphism may inform the reading of such language. Understanding the body and body language necessitates an understanding of the culture that produced the language. The references to God’s head and hands in Psalms correspond to a broader ancient Israelite emphasis on God’s communication and action.